Stylistic Features of Political Discourse: A Linguistic and Functional Perspective - Salimova Bakhora Khurbonovna (International Journal of Formal Education, 2025)
Political discourse serves as a strategic communicative tool designed to influence, legitimize, and mobilize. Its stylistic features—rhetorical strategies, lexical framing, and syntactic constructions—are crucial in achieving persuasive power and ideological influence. This article explores the main stylistic features of political discourse using examples from notable political speeches, including those by Winston Churchill, Barack Obama, and Donald Trump. It analyzes how these stylistic tools function to construct political realities, shape public opinion, and express or mask authority.